Reasons and diagnostic errors in cases of the peripheral nerves of extremities injuring - Vishnevskiy, V. O. (Zaporozhye Medical Journal, 2014)
Trauma of peripheral nerves of extremities takes leading place in disability cases (28-75%). The risk zones for injuring the nerves of upper extremity are shoulder and forearm, and of lower extremity are lower third of the thigh and the upper third of the tibia. The aim of research: to analyze and identify the causes of diagnostic errors and complications in injuries of peripheral nerves of the extremities. Material and methods: Results of clinico-neurological and electrodiagnostical studying of 72 patients with injuries of upper and lower extremities are presented in the article. Patients were treated in 2010-2013 in traumatology department of Dnepropetrovsk state clinical hospital № 16. The author distinguishes three forms of disturbance of the integrity of the neural trunk and five periods of their clinical course: neurotmesis - complete or partial break patterns of nerves, was diagnosed in 43 patients (59,7%); aksonotmesis - break part of axial cylinder, while maintaining the integrity of the epineurium - in 19 patients (26,4%) and neuropraxia - fine-grained lesions without violating the integrity of the axle of cylinders in 10 patients (13.9%). The types of peripheral nerve injuries of extremities were divided into 2 groups: primary and secondary (iatrogenic). Results The study showed that the most frequently pain from the injured nerves of the upper limb radiated at shoulder level, median and ulnar - at the level of the forearm. Diagnostic and therapeutic errors were detected at all stages of medical care, the author noted the insufficient assessment of neurological risk, in the pre-hospital and hospital stages, especially in cases of combined injuries. It is necessary to conduct more thorough clinical, radiological and electrophysiological assessment in the presence of small stab and cut wounds of the extremities. Lack of the special tools and equipment, insufficient qualification of surgeons in matters of anatomical and topographical relationships between nerves, tendons and blood vessels in the soft tissues, as well as divergent views in the specialized literature, about terms of surgical and conservative treatment, about indications for them, leave the problem of peripheral nerve injuries is very topical issue of modern medicine. Conclusions Trauma of peripheral nerves of extremities takes the leading place in permanent disability (28-75%) and occurs in 1,5 - 3,5 % of the total traumatism. Currently, the diagnosis and treatment of peripheral nerves of extremity has no generally accepted standardized system for assessing the level, degree and nature of the injury. In our opinion, the distribution of patients in our study into groups by the etiology and levels of damage the peripheral nerves, helped to clarify and to objectify the reasons for their traumatization, and find errors on the stages of diagnosis and treatment. Most commonly of the radial nerve trunks (45,8%), and on the forearm - the median and ulnar nerves (15,3%) are damaged.